Drugs Repurposing of Molecules Modulating Human Delta Globin Gene Expression via a Model of Transgenic Foetal Liver Cells: Implications for Beta-Hemoglobinopathy Therapeutics - Michela Simbula; Maria Francesca Manchinu; Stefania Olla; Michela Congiu; Simona Vaccargiu; Cristian Antonio Caria; Daniela Poddie; Maria Serafina Ristaldi (Biomolecules)
Beta-hemoglobinopathies such as beta-thalassemia and sickle cell disease are severe genetic blood disorders affecting the beta globin chain of haemoglobin A (α2β2). Activation of delta globin, the non-alpha globin of HbA2 (α2δ2), could represent a possible approach to improve the clinical severity of these pathologies. Notably, the therapeutic potential of delta globin has been demonstrated in previous studies using a mouse model of beta-thalassemia and sickle cell disease. The present study evaluated delta globin gene activation by small molecules in erythroid cells isolated from transgenic murine foetal liver. A screening of 119 molecules, selected for their potential in drug repurposing, was performed without prior selection based on specific pathways of interest. Three candidates—Nexturastat, Stattic and Palbociclib—were found to have high efficacy on delta globin expression. Palbociclib also proved effective in increasing gamma globin expression. All of these compounds have pharmacokinetic profiles that are beneficial for clinical application, providing potential inducer agents of HbA2 that could have therapeutic effects in the treatment of beta-hemoglobinopathies.